Removal of Cu2+ Ions from Aqueous Solutions Using Copper Resistant Bacteria - Rajeshkumar, R.; Kartic, N. (Our Nature, 2012)
Biosorption using resistant microorganisms is an effective process for treatment of industrial effluents and removal of heavy metals from contaminated sites. In this study copper resistant bacteria from fireworks industrial contaminated soil were isolated, enumerated and characterized. The tolerances of the organisms decreased with increase in the copper concentration. The isolated bacterial strain was identified as Bacillus sp. and was resistant to 300 mg/L of copper concentration. Biosorption studies were carried out in the Bacillus sp. The optimum temperature was determined to be 35°C and pH was 8.0. The maximum removal of 88% was obtained at optimum conditions when the initial copper ion concentration was 100 mg/ L. Hence the Bacillus sp. isolated proved to be an efficient biosorbent. DOI: http://dx.doi.org/10.3126/on.v9i1.5733